Burnout in medical students: a systematic review. (8th July 2013) - IsHak, Waguih; Nikravesh, Rose; Lederer, Sara; Perry, Robert; Ogunyemi, Dotun; Bernstein, Carol
Summary Background Burnout is a state of mental and physical exhaustion related to work or care‐giving activities. Distress during medical school can lead to burnout, with significant consequences, particularly if burnout continues into residency and beyond. The authors reviewed literature pertaining to medical student burnout, its prevalence, and its relationship to personal, environmental, demographic and psychiatric factors. We ultimately offer some suggestions to address and potentially ameliorate the current dilemma posed by burnout during medical education. Methods A literature review was conducted using a PubMed/Medline, and PsycInfo search from 1974 to 2011 using the keywords: 'burnout', 'stress', 'well‐being', 'self‐care', 'psychiatry' and 'medical students'. Three authors agreed independently on the studies to be included in this review. Results The literature reveals that burnout is prevalent during medical school, with major US multi‐institutional studies estimating that at least half of all medical students may be affected by burnout during their medical education. Studies show that burnout may persist beyond medical school, and is, at times, associated with psychiatric disorders and suicidal ideation. A variety of personal and professional characteristics correlate well with burnout. Potential interventions include school‐based and individual‐based activities to increase overall student well‐being. Discussion Burnout is a prominent force challenging medical students' well‐being, with concerning implications for the continuation of burnout into residency and beyond. To address this highly prevalent condition, educators must first develop greater awareness and understanding of burnout, as well as of the factors that lead to its development. Interventions focusing on generating wellness during medical training are highly recommended.